"Evaluación de fungicidas para el manejo del añublo de la vaina (Rhizoctonia solani Kuhn) en el cultivo de arroz )Oryza satica L) variedad F50 en la zona de Babahoyo Provincia de los Ríos. - Roldan González, Franklin Valentino (2013)
This research was conducted from September 2010 to February 2011 and was held in Mr. Javier Mejia terreno del located in "Los Almendros" to the outskirts of Babahoyo km 10 route to Montalvo, Rivers Province. The site is located between the geographical coordinates, latitude 1 º 50 '51 "west longitude and 79 º 30' with a height 60 meters above sea level. The climate is tropical humid forest (bh-T) characterized by an average temperature of 24.8 º C, annual rainfall of 2057.5 mm, relative humidity of 82% heliophany 1000 hours / light / year. The topography is flat and the soil texture is clay loam with a pH of 5.7. Raised general objective assess the efficiency of fungicides for management of sheath blight (Rhizoctonia solani) in rice (Oryza sativa) variety Fedearroz 50 Babahoyo area, province of Los Rios. Experimental design was used randomized complete block (RCBD) with 6 treatments and 4 replications. The variables were subjected to analysis of variance and to establish the statistical difference between the means of variables, we used the Tukey test at 5% probability. To determine the effects of fungicides evaluated the incidence and severity of sheath blight, percentage of healthy grains, vain, stained, total grains per panicle, 1000 grain weight and yield. Based on the analysis and interpretation of the results it is concluded that the application of fungicides positively influenced the decrease the incidence and severity of disease, and improved healthy grains number per spike, and the number of applications was given based on the two stages of the crop susceptibility are DDS 50 and 70 depending on the variety of rice. Most grains per panicle was obtained in treatments including Silvacur Taspa and the composition (Difeconazole + propiconazole) introduce greater efficiency in the management of sheath blight the highest grain yield was obtained with treatment Taspa (Difeconazol + propiconazole) and also with Silvacur fungicide (tebuconazole + triadimenol) for its effective control of the disease the higher marginal utility came with the application Taspa with USD $ 1003.07 USD 1064.53 and above the control without fungicide application .